The Ritual of Azazel in the Jewish Tradition and Osu Caste System in Igbo Tradition: Any Nexus? - Rowland Onyenali (Journal of Comparative Study of Religions, 2025)
In today’s African society, there is a sudden surge in interest in Indigenous African Spiritualities (IAS). This interest is mainly among the youth. This surge seems to come face to face with the Judeo-Christian tradition which has taken strong root in Africa. In some cases, the return to IAS seems to challenge the long-age accepted teachings and dogmas of the Judeo-Christian faith. This return to IAS is because of the feeling of the youth that the Judeo-Christian faith does not address some of their pressing needs like issues of insecurity, the question of theodicy, financial issues, etc. When they read through the scriptures of the Judeo-Christian tradition, they fail to see much connection between what these scriptures teach and the accepted beliefs of IAS. The paper argues for a connection between the teachings of the Jewish scriptures and IAS in one core aspect. It adopts a historical and cross-cultural methodology to come to the conclusion that the Azazel ritual of the Jewish Testament has a counterpart in the Osu caste system of the traditional Igbo religion. This is especially so in the propitiatory function of the two rituals.